Do the poor living in Jakarta have better advantages than other cities in Indonesia? Analysis of economic status on utilization of primary health care - Husna, Asmaul; Hasanbasri, Mubasysyir (BKM Public Health and Community Medicine, 2021)
Purpose: This study aims to examine whether primary health care (PHC) services in Indonesian cities are utilized exclusively by the poor or also by the non-poor. If both groups access PHC, it may indicate that the system promotes equity by providing inclusive, non-discriminatory services. Methods: This study analyzed the utilization of primary health care (PHC) among individuals aged 15 years and older in 13 major cities in Indonesia, using data from the Indonesian Family Life Survey 5 (IFLS5), conducted in 2014. The equity effect was assessed by comparing the proportion of PHC users between poor and non-poor population groups. Results: The proportion of the population utilizing primary health care (PHC) increased by 26% in the past four weeks. Among the five major urban areas in Indonesia, Jakarta demonstrated the most equitable utilization of PHC services between poor and non-poor groups. In Jakarta, the poor were more likely to use PHC services, with an odds ratio (OR) of 1.3 (95% confidence interval [CI]: 1.04–1.83). Conclusion: Jakarta demonstrates the most equitable access to health services between poor and non-poor populations among major Indonesian cities. These findings align with primary health care (PHC) reform efforts and support the policy objective of improving access to health facilities for the poor.